Web banking layout effects on consumer behavioural intentions - Vrechopoulos, Adam; Atherinos, Evagelos (International journal of bank marketing, 2009)
Purpose - Elaborating on earlier research by Vrechopoulos et al., this paper aims to investigate web banking store layout effects on user-consumer behaviour and to report on a laboratory experimental investigation into user acceptance of three different layout types.Design methodology approach - A web banking store was developed in three versions equal to the number of the alternative layouts manipulated by the laboratory experimental design. Two layout types were transformed from conventional banking and one type was designed by incorporating users' preferences and suggestions. The relationships in technology acceptance model (TAM) in the three treatments are tested separately, and then the subjects' evaluations on TAM constructs are compared.Findings - The findings imply that store layout affects online consumer behaviour, confirming the findings of Vrechopoulos et al. in a different sector. The study also confirms the TAM relationships in all treatments and indicates that layout has an effect on user acceptance of web banking in terms of TAM constructs.Research limitations implications - This study confirms the available knowledge regarding a store layout's influencing role on consumer behaviour in the context of web commerce.Practical implications - Direct managerial implications for web banking are provided through the design of the "improved future" layout, which is depicted in the form of an abstract interface design.Originality value - The paper adopts an innovative conclusive causal research design towards testing the research hypotheses. To that end, an experimental application was developed in the laboratory and the research hypotheses were "packed-up" with references from different disciplines (i.e. marketing and information systems) providing through that an interdisciplinary nature on the present study.